2014
DOI: 10.1136/bjophthalmol-2013-304765
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between retinal sensitivity assessed by microperimetry and contrast sensitivity in diabetic macular oedema

Abstract: CS and RS showed moderately significant correlations in CSME. However, neither CS nor RS was correlated with RT in patients with CSME. It could be that CS and MP are complementary to each other and are useful tools in the evaluation of functional vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Retinal thinning has been suggested to correlate with retinal dysfunction in diabetic patients. 23 , 35 , 36 , 44 Similar to previous studies, we found structural evidence of retinal neurodegeneration by the thinner GCL+IPL in diabetic patients. 10 , 25 , 30 , 31 , 35 We also found that diabetes differentially affects other layers of the retina.…”
Section: Discussionsupporting
confidence: 90%
“…Retinal thinning has been suggested to correlate with retinal dysfunction in diabetic patients. 23 , 35 , 36 , 44 Similar to previous studies, we found structural evidence of retinal neurodegeneration by the thinner GCL+IPL in diabetic patients. 10 , 25 , 30 , 31 , 35 We also found that diabetes differentially affects other layers of the retina.…”
Section: Discussionsupporting
confidence: 90%
“…It is being increasingly used to monitor a variety of conditions including CHM, achromatopsia, AMD, and diabetes 5,710. It has been correlated to contrast sensitivity11 as well as to optical coherence tomography (OCT) appearance 12. The anticipated potential benefits of using microperimetry as an outcome measure in CHM gene therapy clinical trials include accurate threshold sensitivity mapping at individual retinal points over time (e.g., in the region exposed to a subretinal delivery of viral vector), and automated adjustments for eye movements that may compensate for fixation losses related to poor VA.…”
mentioning
confidence: 99%
“…Contrast sensitivity and RS are considered to be complementary tools in functional vision evaluation in DME. 20 Vujosevic et al 21 have previously found macular microperimetry to be an excellent additional tool to add to BCVA and CMT as a factor explaining visual function in patients with DME; they had also demonstrated a significant change in microperimetry results in patients with normalizing macular thickness in center-involving DME. Mastropasqua et al 22 have found that RS, as measured by microperimetry, improved after dexamethasone implantation as early as 1–4 months after the injection.…”
Section: Discussionmentioning
confidence: 99%